Q-CASA Invited Speaker Structured noise in quantum computers: an obstacle or an opportunity? - Kapit, Eliot (2023 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW), 2023)
The single greatest challenge in building workable quantum computers is noise, arising from uncontrolled interactions between qubits and their surrounding environment. In superconducting circuits-one of the most advanced, and broadly studied, qubit modalities-this noise has distinctive spectral features that are fairly universal across a wide array of qubit designs. In recent years, clever techniques to exploit this structure through the use of AC driving, coupling to intentionally lossy objects, and strong qubit-qubit interactions have led to innovative new qubit designs that would be impractical or even impossible in other platforms. In this talk, I provide an overview of important new results in this area, with special focus on two recent advances from my group. First, I will discuss the Star Code, a fully autonomous error correction protocol using just two tunably coupled transmon qubits, which was successfully demonstrated in a recent experiment. Second, I will describe the Cold Echo Qubit architecture, which consists of two or three strongly coupled flux-type qubits subject to strong, continuous AC drives, suppressing all single qubit error channels in a similarly autonomous manner. Finally, I will sketch how these devices might be incorporated as an autonomous "base layer" of a larger digital error correction code, and how the core principles of their operation can inspire novel quantum algorithms for quantum simulation and optimization.